Comparison Of Some Estimation Methods For The Estimators Of Marshall Olkin Distribution With Simulation - Najlaa Ali Dhumad; Abbas Lafta Kneehr (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
The research comprised multiple simulated tests to determine the relationship between (sample size, distribution parameter value, estimation method, and pollution indivuduales). The experimental findings indicate that the estimator is influenced by sample size, the value of distribution parameter, estimation method, and pollution indivuduales. The results of the mean square error analysis indicate that (robust estimation method) produces the best results with the lowest mean square error, and the best estimation method was (191) of (243) simulation experiments. Additional statistical distributions with additional factors can be performed to demonstrate additional results.